2018
DOI: 10.1073/pnas.1812770115
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the structure of the condensin protein complex

Abstract: Published under the PNAS license.Data deposition: The atomic coordinates of both open and closed condensin protein complex have been deposited in the Model Archive database, https://modelarchive.org/ (Model Archive ID codes ma-abc6s and ma-ac7jp).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…DCA gives structural information once we realize that the residue pairs that evolve in a correlated way, as revealed by multiple sequence alignments, are likely to be spatially proximate in at least one structure of the conformational ensemble. DCA has already been used to obtain predictions of bacterial SMC protein structures (19,20), but coevolutionary information about the coiled coils is somewhat sparse. To understand the coiled-coil structural dynamics, we therefore also employed an optimized transferable coarse-grained protein force Significance SMC−kleisin protein complexes play an important role in establishing the 3-dimensional organization of DNA in cells.…”
Section: Dna Topologymentioning
confidence: 99%
“…DCA gives structural information once we realize that the residue pairs that evolve in a correlated way, as revealed by multiple sequence alignments, are likely to be spatially proximate in at least one structure of the conformational ensemble. DCA has already been used to obtain predictions of bacterial SMC protein structures (19,20), but coevolutionary information about the coiled coils is somewhat sparse. To understand the coiled-coil structural dynamics, we therefore also employed an optimized transferable coarse-grained protein force Significance SMC−kleisin protein complexes play an important role in establishing the 3-dimensional organization of DNA in cells.…”
Section: Dna Topologymentioning
confidence: 99%
“…Recent single-molecule experiments revealed that the budding yeast condensin is a molecular motor [6] that extrudes a DNA loop [7,8]. However, the detailed molecular mechanism of DNA-loop extrusion by condensin and other members of the SMC protein family remains unclear [8][9][10] and has been an ambitious target of computational modeling studies [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…DNA looping plays a set of diverse and critical roles. In cells, DNA loops can activate or repress genes in prokaryotes (1)(2)(3)(4), organize and compact the genome in eukaryotes (5)(6)(7)(8)(9), or compact the entire genome in a sequence-independent manner in sperm and bacteria (10)(11)(12)(13). In DNA nanoengineering, synthetic looping proteins have allowed for self assembly of DNA-protein nanostructures (14).…”
Section: Introductionmentioning
confidence: 99%